Perbedaan Jumlah Sel Sertoli Pasca Pemberian Ekstrak Etanol Akar Purwoceng (Pimpinella alpina) - ANNISA FARAH FADHILAH; FITRANTO ARJADI; NUR SIGNA AINI GUMILAS (Gunung Djati Conference Series, 2022)
Paradoxical Sleep Deprivation (PSD) is one form of stress models in laboratory animals resulting in oxidative stress. Oxidative stress can decrease the number of Sertoli cells. Ethanol extract of purwoceng roots containing active substances for proliferation of Sertoli cells is expected to increase the number of Sertoli cells. Objective: To determine differences in the number of Sertoli cells after administration of ethanol extract of purwoceng roots in male rats after stress model of PSD induction. Method: This was an experimental research with posttest only with control group design. Thirty rats were divided into six groups: group A (negative control), group B (PSD with 7 days sleep recovery), group C (PSD), group D (PSD with 16.75 mg/ml/200grBB of ethanol extract of purwoceng roots), group E (PSD with 33.50 mg/ml/200grBB of ethanol extract of purwoceng roots), and group F (PSD with 50.25 mg/ml/200grBB of ethanol extract of purwoceng roots). Induction of PSD conducted for 96 hours and followed by administration of ethanol extract of purwoceng roots for 7 days. Result: The number of Sertoli cells in group A had the highest rates (29,17±3,58), followed by group D (28,77±3,16), group E (27,66±2,51), group B (27,45±1,45), group F (27,44±1,71), and group C (27,29±1,54). Kruskal-Wallis test showed the value of p=0,858. Conclusion: There was no significant difference in the mean number of Sertoli cells of male white rats after administration of various doses of ethanol extract of purwoceng roots.